Contributions to Mineralization - Ismail Al-Juboury, Ali (IntechOpen, 2018)
Contributions to Mineralization provide some new aspects on economically important mineral deposits from various locations in Asia, Africa, and Europe in terms of their genesis, geochemical, and age considerations. Mining industry and mineral engineering issues are also discussed in the book through some new statistical approaches and economic aspects. The book represents a useful guide for specialists in the fields of mineralogy, economic geology, mining engineering, environmental impacts, and mining industry.